Macroeconomic Effects of Social Security and Tax Reform in the United States - Bayoumi, Tamim (IMF Working Papers; Working Paper, 2005)
We use the IMF's Global Fiscal Model to evaluate recent proposals to reform social security and the tax system in the United States. Introducing personal retirement accounts is unlikely to yield significant macroeconomic benefits unless it spurs additional fiscal consolidation to prevent a large increase in government debt. Similar benefits are obtained if the social security surplus is placed in a lockbox while maintaining the same debt target. Lowering the taxation of investment income is beneficial, but only if the reform is revenue neutral. Debtneutral social security and tax reform in the United States has large positive effects on the rest of the world.